2011
DOI: 10.1590/s1413-35552011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Does the BODE index reflect the level of physical activity in daily life in patients with COPD?

Abstract: Objectives: To study the relationship between the level of physical activity in daily life and disease severity assessed by the BODE index in patients with chronic obstructive pulmonary disease (COPD). Methods: Sixty-seven patients with COPD (36 men) with forced expiratory volume in the first second (FEV 1 ) of 39 (27-47)% predicted and age of 66 (61-72) years old were evaluated by spirometry, dyspnea levels (measured by the Medical Research Council scale, MRC) and by the 6-minute walking test (6MWT). The BODE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…Our results meet the with an increase of mortality and exacerbation rates in patients with COPD (28,29,30).…”
Section: Discussionsupporting
confidence: 88%
“…Our results meet the with an increase of mortality and exacerbation rates in patients with COPD (28,29,30).…”
Section: Discussionsupporting
confidence: 88%
“…Patients hospitalized for CAP presented lower performance on the 6MWT (66% of predicted), indicating a reduction in FC, as previously demonstrated in patients with stable COPD [22][23][24] . In a study by Solh et al 7 , elderly patients hospitalized for CAP showed a decline in functional capacity as assessed by an ADL scale.…”
Section: Discussionsupporting
confidence: 75%
“…These authors also concluded that BMI was not a determining factor for PADL level. Other studies also did not find BMI to be a strong correlate of the level of physical activity in daily life in patients with COPD [9,32,33].…”
Section: Discussionmentioning
confidence: 88%